2014
DOI: 10.1002/lary.24840
|View full text |Cite
|
Sign up to set email alerts
|

The role of elective neck dissection in early stage buccal cancer

Abstract: END was suggested in T1-T2N0 buccal cancer to improve the neck control rate. In patients for whom END is not performed at the time of tumor excision, regular follow-up of neck status is necessary because the metastatic lesions are mostly salvageable and do not influence the OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…Thirty‐nine studies assessed occult nodal metastasis in patients with cN0 T1 and T2 of oral SCC who underwent END (Table ), with five RCTs and 34 retrospective studies. The rate of occult metastasis in patients with cN0 ranged from 20.6% to 49% in the RCTs, and 7.3% to 39.2% in the retrospective series.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty‐nine studies assessed occult nodal metastasis in patients with cN0 T1 and T2 of oral SCC who underwent END (Table ), with five RCTs and 34 retrospective studies. The rate of occult metastasis in patients with cN0 ranged from 20.6% to 49% in the RCTs, and 7.3% to 39.2% in the retrospective series.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13] Overall incidence of occult nodal disease in cT1N0 oral cavity SCC is 15.1%, with the lowest risk (5.9%) in welldifferentiated tumors. To a lesser degree, there may be a link between female sex and occult disease, although, relative to tumor differentiation, the strength of association with these 2 variables was not as strong.…”
Section: Discussionmentioning
confidence: 99%
“…2 Recent prospective evidence from D'Cruz et al 3 on cT1-2N0 oral cavity SCC demonstrated significantly improved survival with up-front elective neck dissection (END) versus observation and therapeutic neck dissection for cT2N0 oral cavity SCC. [2][3][4][5][6][7][8][9][10][11][12][13] Currently, no large studies of occult nodal disease in cT1N0 oral cavity SCC exist. However, this survival benefit was equivocal in their cT1N0 cohort (44.2% of their study), accentuating the importance of reserving END for those The National Cancer Data Base (NCDB) is a joint project of the Commission on Cancer of the American College of Surgeons and the American Cancer Society.…”
Section: Introductionmentioning
confidence: 99%
“…Although these primary tumors may be well controlled by surgical resection, a neck dissection is necessary when there is evidence of lymph node metastasis [5, 6]. However, there are no cancer cells in the cervical lymphatic tissues in some patients.…”
Section: Introductionmentioning
confidence: 99%